2020
DOI: 10.1021/acsnano.0c00910
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Magnetic Nanocatalysts Drive Starvation–Chemodynamic–Hyperthermia Synergistic Therapy for Tumor

Abstract: Magnetic hyperthermia therapy (MHT) has been considered as an excellent alternative for treatment of deep tumor tissue; however, up-regulation of heat shock proteins (HSPs) impairs its hyperthermal therapeutic effect. Reactive oxygen species (ROS) and competitive consumption of ATP are important targets that can block excessive HSP generation. We developed a magnetic nanocatalytic system comprised of glucose oxidase (GOD)-loaded hollow iron oxide nanocatalysts (HIONCs) to drive starvation–chemodynamic–hyperthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 50 publications
3
84
0
Order By: Relevance
“…[ 3 ] In addition, nanoplatforms can be designed to have tumor microenvironment (such as acidic pH, glutathione, enzyme, or reactive oxygen species (ROS))‐responsive drug release profile to maximize the tumor therapy effect. [ 4 ] Furthermore, various inorganic or organic–inorganic hybrid platforms with photothermal, catalytic, or ultrasound responsiveness have been developed to achieve photothermal therapy (PTT), [ 5 ] chemodynamic therapy, [ 6 ] or sonodynamic therapy. [ 7 ] Importantly, by combination of an immunotherapeutic component, nanoplatforms can be designed to boost tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In addition, nanoplatforms can be designed to have tumor microenvironment (such as acidic pH, glutathione, enzyme, or reactive oxygen species (ROS))‐responsive drug release profile to maximize the tumor therapy effect. [ 4 ] Furthermore, various inorganic or organic–inorganic hybrid platforms with photothermal, catalytic, or ultrasound responsiveness have been developed to achieve photothermal therapy (PTT), [ 5 ] chemodynamic therapy, [ 6 ] or sonodynamic therapy. [ 7 ] Importantly, by combination of an immunotherapeutic component, nanoplatforms can be designed to boost tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 113 ] Copyright 2019, American Chemical Society. d) Schematic illustrating the biological significance of the Fenton and Haber–Weiss reactions.…”
Section: Nanomaterials‐based Nanoplatforms For Combination Therapy Of Cdt With Other Therapeutic Modalitiesmentioning
confidence: 99%
“…For example, a magnetic nanocatalytic system, comprised of GOx‐loaded hollow iron oxide nanocatalysts (HIONCs), was developed to simultaneously drive starvation, chemodynamic, and MHT for tumor treatment (Figure 8c). [ 113 ] The Fe 2+ of HIONCs possesses catalytic activity both in producing ROS via the Fenton reaction and in producing O 2 via the decomposition of H 2 O 2 . The generation of O 2 would relieve hypoxia and promote GOx to catalyze the conversion of intratumoral Glu into gluconic acid and H 2 O 2 .…”
Section: Nanomaterials‐based Nanoplatforms For Combination Therapy Of Cdt With Other Therapeutic Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Fe 3+ on the surface of NPs converted into Fe 2+ by reacting with GSH, catalyzing the Fenton reaction to enhance magnetic hyperthermia. In yet another study, the further loading of GOD not only resulted in starvation therapy but also generated more H 2 O 2 at the tumor, resulting in synergistic starvation-chemodynamic-hyperthermia tumor therapy [ 219 ]. Lastly, one study showed that in graphene oxide-grafted magnetic manorings, the elaboration of ferrimagnetic vortex-domain iron oxide nanoring and graphene oxide exhibited efficient thermal conversion and amplified the Fenton reaction-induced ROS level significantly under an alternating magnetic field [ 220 ].…”
Section: Fenton and Fenton-like Reactions-mediated Combination Therapymentioning
confidence: 99%